PENGARUH KEPEMIMPINAN, KOMUNIKASI DAN PEMBERIAN REWARD TERHADAP KINERJA PEGAWAI BADAN KOORDINASI WILAYAH II BOJONEGORO PEMPROV JATIM MELALUI MOTIVASI KERJA - Eko Wahyu Hidayat Udjut Saputra; Mei Indrawati; Woro Utari (Badung: LPPM Universitas Triatma Mulya, 2021)
The purpose of this study was to describe the leadership, communication, reward, work motivation and performance of employees in the Bojonegoro Regional Coordinating Board for the East Java Provincial Government. To determine and analyze the influence of leadership, communication, reward on motivation. The influence of leadership, communication, reward, motivation on performance. The influence of leadership, communication and reward on performance through motivation. The population in this study were employees of the Regional Coordinating Board II of Bojonegoro, East Java Provincial Government, amounting to 34 people with a sample of 33 people. Data collection techniques using questionnaires and documentation. The data analysis technique used path analysis. The results of the study can be explained that the performance of employees is in very good condition, while for work motivation, leadership, communication and reward are in good condition. Leadership and giving rewards do not have a significant effect on motivation. Communication has a significant effect on motivation. Leadership, communication and motivation have a significant effect on performance. Rewards do not have a significant effect on performance. Leadership and rewarding do not have a significant effect on performance through motivation. Communication has a significant effect on performance through motivation.